PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS (Studi Pada Perusahaan Jasa Subsektor Transportasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018) - Susilawati Kurnia; Kamaliah Kamaliah; Kurnia Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research is to test the influence of liquidity, leverage and profitability, to financial distress on transportation subsector service companies listed on the Indonesia Stock Exchange in the period of year 2016-2018. Data analysis techniques in this study using descriptive methods, sampling techniques used with purposive sampling method so that the research samples obtained as much as 17 financial distress companies with the amount data observed as many as 51 observations. The result of the research that current ratio has an effect on financial distress with a significance value of 0.048 < 0.05. Debt to equity ratio has on effect on financial distress with a significance value of 0.018 < 0.05. Return on asset has no effect on financial distress with a significance value of 0.673 > 0.05.Keyword: Liquidity, Leverage, Profitability, Financial Distress